Análise experimental e numérica de um talude em solo residual submetido à variação das condições hidráulicas - Lins, Jorge Henrique Ribeiro (2022)
The economic and social development of a region necessarily involves the development of an infrastructure that allows its proper use and occupation, being common works of cut and fill for road or occupation purposes. It is of special interest to Geotechnics to study the behavior of slopes derived from such terrain adaptations. In the Brazilian context, the prevalence of tropical soils and their unsaturated condition add more complexity to the study, adding the suction variable to the stress state analysis. For these soils, the most common agent promoting deformation and loss of strength is the advance of the wetting front due to rainfall. Thus, it is essential to verify the influence of rainfall on slope behavior in tropical conditions. In view of the previous exposition, the present study aims to analyze the hydromechanical behavior of a road slope formed by residual and unsaturated soil, in a laboratory stage of parameter determination, followed by numerical modeling. Experiments were carried out to determine strength parameters (effective friction angle and cohesion), hydraulic and relative to the unsaturated condition (retention curve and angle that relates strength and cohesion), added to the characterization tests (granulometry, Atteberg limits and void index). In the numerical study, we sought to visualize the influence of precipitation and hydraulic parameters (retention curve and saturated hydraulic conductivity) on the pore pressure distribution inside the slope and on its stability. After the numerical step, it was found that the different precipitation characteristics (intensity and duration) increased the pore pressures and decreased the strength of the material, as expected. However, it was not enough to trigger any rupture in the slope studied. For the hydraulic parameters, their critical roles in percolation through the massif and how this is reflected in the calculations of safety factors were verified.